Elevação do teor superficial de nitrogênio no aço inoxidável austenítico ISO 5832-1 - Reis, Ricardo Fernando dos (2007)
The insertion of nitrogen in stainless steel has been studied since 1925. When in solid solution it produces a few effects such as: increase in mechanical strength, hardness, resistance to fatigue, to wear and corrosion. Although benefic effects of nitrogen on the proprieties of steel are well known, the introduction of this element in high amounts is not trivial. The present work discussed a sequence of procedures involving plasma nitriding and solubilization, aiming at superficial enrichment of nitrogen in commercial austenitic stainless steel (ISO 5832-1). Three nitriding temperatures (630, 750 and 870 ºC) and three times (1h, 3h and 5h) were studied, totaling nine different nitriding conditions. For three of these, solubilization parameters were studied, aiming at obtaining layers with nitrogen in solid solution. After processing, the samples were characterized by microhardness, X - ray diffraction, optical and electronic microscopy, grain size measurement, mass variation, energy dispersive spectrometry (EDS), wavelength dispersive spectrometry (WDS), magnetic and superficial roughness measurements. It was verified that for nitriding in elevated temperatures (750 and 870 ºC) the growth of the compound layer presented diffusive behavior and that the increase in temperature formed smaller amounts of chromium nitrides, also promoting the disappearance of iron nitrides from the surface of the material. The solubilization parameters depend on the thickness, morphology and stability of the nitrides present in the nitride layer. It was also verified that the glow discharge processing of polished samples (Ra = 0.07 µm) in the cathode configuration increased roughness, however it did not affect the wetting angle. According to this processing route, layers enriched with 0.45% wt of nitrogen were obtained for depths up to 450 µm, inducing the initial value of PREN (28.11) to increase to 34.11. This modification indicated improved pitting corrosion resistance. The hardness of the material also significant increased, from 208 to 271 HV0.05.